(untitled) (Colombia Medica, 1989)
116 case histories were analyzed from patients with obstructive biliary tract disease in 1983. The mean age was 57; 63% of patients were older than 40, and a female/male ratio of 2.3:1. The most frequent symptoms and signs were nausea, vomiting, right upper quadrant pain, and jaundice. An obstructive pattern by laboratory testing could be demonstrated in only 50-60% of cases. In many cases, laboratory data from the case histories were unavailable. Oral cholecystogram was performed in 16% of cases; gallbladder ecography in 27%; and transparietal hepatic cholangiography in 20% of patients. This corroborates that clinical evaluation, despite diagnostic tools, is still the main diagnostic method. The most commonly performed operation was cholecystectomy and CBDE. The most frequently isolated bacteria were Escherichia coli, Klebsiella pneumoniae, and Enterobacter cloacae. A subhepatic drain was left in 21% of cases. Postoperative complications were present in 45% of cases, and the most common ones were septic shock-residual stones and wound infection; 20 patients died for a mortality rate of 17.2%